Additions and corrections - Blackburn, David C.; Wake, David B. (Zootaxa, 2012)
Recently, we published an invited contribution to Zootaxa in which we summarized the classification of subfamilies, families, and orders of living amphibians (Blackburn & Wake 2011). Here we contribute minor corrections and additions.